Retransplanting a previously transplanted kidney: A safe strategy in times of organ shortage?. Issue 3 (15th December 2021) - Karakizlis, Hristos; van Rosmalen, Marieke; Boide, Philipp; Askevold, Ingolf; Vogelaar, Serge; Lorf, Thomas; Berlakovich, Gabrielle; Nitschke, Martin; Padberg, Winfried; Weimer, Rolf
Abstract: Background: The shortage of organs for transplantation remains a global problem. The retransplantation of a previously transplanted kidney might be a possibility to expand the pool of donors. We provide our experience with the successful reuse of transplanted kidneys in the Eurotransplant region. Methods: A query in the Eurotransplant database was performed between January 1, 1995 and December 31, 2015, to find kidney donors who themselves had previously received a kidney graft. Results: Nine out of a total of 68, 554 allocated kidneys had previously been transplanted. Four of these kidneys were transplanted once again. The mean interval between the first transplant and retransplantation was 1689±1682 days (SD; range 55–5, 333 days). At the time of the first transplantation the mean serum creatinine of the donors was 1.0 mg/dl (.6–1.3 mg/dl) and at the second transplantation 1.4 mg/dl (.8–1.5 mg/dl). The mean graft survival in the first recipient was 50 months (2–110 months) and in the second recipient 111 months (40–215 months). Conclusion: Transplantation of a previously transplanted kidney may successfully be performed with well‐preserved graft function and long‐term graft survival, even if the first transplantation was performed a long time ago. Such organs should be considered even for younger recipients in carefully selected cases.